The Impact of Renaming STT Telkom being Telkom University to Image of Telkom University - Kirianawati, Felesia Ekafaya (Universitas Muhammadiyah Yogyakarta, 2015)
Telkom University is one of university in Bandung, was established on August 14, 2013. Telkom University was transformed of STT Telkom which standing on 1990. Based on observation which held by researcher, many people still consider that Telkom University still same with STT Telkom. But actually the case is Telkom University have different identity with STT Telkom. That’s problem surely will be influence to image of Telkom University. This research have purpose to know how the relation name changes of STT Telkom being Telkom University about image of Telkom University to Bandung society. The theories used in this research are the public relation theory as a grand theory, rebranding theory as a middle theory, and then renaming theory and corporate image theory as an applied theory. This study is using the assosiatif methods, that is to find relation about independent variable and dependent variable. Using with survey methods to the 200 Bandung society as the respondents were selected using multistage of cluster sampling techniques. To determine the relation both of this variable in this research, used deskriptive techniques, pearson correlation techniques and also regression technique. The result showed that there are positive relation and significant between renaming of STT Telkom being Telkom University to image of Telkom University in Bandung Society.